METODE KOLABORATIF DALAM MENINGKATKAN KETERAMPILAN BERBAHASA ARAB PADA MAHASISWA DI ASRAMA PUTRI STAI AL-FURQAN MAKASSAR [COLLABORATIVE METHODS IN IMPROVING ARABIC LANGUAGE SKILLS OF STUDENTS IN THE FEMALE DORMITORY OF STAI AL-FURQAN MAKASSAR] - Ismail, Ismail; Erna, Erna; Anatasya, Siti Aulia; Hasbullah, Hasbullah; Idris, Fahrul Islami; Salsabila, Anita Fitria (Al-Ihtiram: Multidisciplinary Journal of Counseling and Social Research, 2025)
Arabic language proficiency plays an important role in deepening Islamic knowledge, especially for students in religious institutions such as STAI Al-Furqan Makassar. Arabic language skills cover four main aspects: listening, speaking, reading, and writing, where speaking skills are often a challenge in themselves. The collaborative method is proposed as a solution to improve students' speaking skills, by emphasizing social interaction and direct practice in the dormitory environment. This study uses a qualitative descriptive approach to describe the application of the collaborative method in the context of informal learning in the female dormitory. The results show that this method not only improves speaking skills, but also builds academic solidarity and social skills. The dormitory environment that supports intensive interaction allows students to practice Arabic naturally and continuously. Thus, developing speaking skills through collaborative methods in the dormitory is an effective and relevant strategy in learning Arabic.